Cellular and transcriptomic responses to a PDE4DIP-directed siRNA in MDA-MB-231 breast cancer cells - Cong Wang; Chunjing Bian; Zhe Wang; Tao Luo (Discover Oncology, 2026)
Abstract PDE4DIP/myomegalin is a Golgi- and centrosome-associated scaffold encoded by a complex, alternatively spliced gene. We examined cellular and transcriptomic responses of MDA-MB-231 cells to a PDE4DIP-directed siRNA. Its 21-nt target site occurs in 40 of 49 protein-coding transcripts under the current RefSeq annotation, including transcript variant 34, which encodes MMG8/SMYLE, and is therefore not unique to the MMG8/SMYLE transcript. The principal 443M-reactive species was an approximately 150-kDa band consistent with MMG8/SMYLE, with no prominent higher-molecular-weight species detected. After equal-density reseeding, siPDE4DIP-treated cells showed lower relative CCK-8 signal at 72 h, but not at 24 or 48 h, and lower wound closure at 24 h. Paired RNA-seq analysis across three experimental blocks identified 67 differentially expressed genes (24 upregulated and 43 downregulated; adjusted P < 0.05 and |log₂ fold change| > 1). Gene set enrichment analysis showed positive enrichment of translation/ribosome programs and negative enrichment of cytoskeletal, small-GTPase, lysosomal, and membrane-trafficking programs. Separately, gene-level PDE4DIP expression was positively associated with CD274 and a five-gene M2-associated marker score in 1,097 TCGA-BRCA primary tumors, with both associations also observed in 141 PAM50 basal-like tumors. These exploratory associations were not mechanistically linked to the cell-based findings. Because only one siRNA and one cell line were used, sequence-dependent off-target effects cannot be excluded, and the findings may not generalize. The shared target site precludes MMG8-specific attribution. Isoform-resolved perturbations and additional breast cancer models are needed for confirmation.